Combination of Low-Dose Gemcitabine and PD-1 Inhibitors for Treatment in Patients With Advanced Malignancies - Huang, Hao; Peng, Ling; Zhang, Bicheng; Till, Brian G.; Yang, Yonghao; Zhang, Xiaojie; Zhao, Lingdi; Fu, Xiaomin; Li, Tiepeng; Han, Lu; Qin, Peng; Chen, Lin; et al. (Frontiers in Immunology, 2022)
Purpose: This study aimed to determine the efficacy of low-dose gemcitabine combined with programmed death-1 (PD-1) inhibitors in the treatment of multiple malignancies, providing a cost-effective and safe treatment option. Study Design: This study included 61 patients with advanced solid tumors treated with low-dose gemcitabine combined with PD-1 inhibitors at Henan Cancer Hospital between January 2018 and February 2022. We retrospectively reviewed medical records to evaluate several clinical factors including progression-free survival (PFS), overall survival (OS), adverse effects (AEs), and objective response to treatment. Results: Sixty-one patients received treatment with low-dose gemcitabine combined with PD-1 inhibitors. Objective response rate (ORR) was 29.5% and the disease control rate (DCR) was 62.3%. Median PFS was 4.3 months (95% confidence interval, 2.3 to 6.3 months) and median OS was 15.0 months (95% confidence interval, 8.8 to 21.2 months). Haematological toxicity, mainly leukopenia or thrombocytopenia, was the most common AE, with any-grade and grade 3/4 haematological toxicity reported in 60.7% and 13.1% of patients, respectively. Conclusions: Low-dose gemcitabine combined with PD-1 inhibitors may offer a novel treatment option for patients with advanced malignancies.